Faktor - Faktor Yang Mempengaruhi Tingkat Kebahagiaan Masyarakat Yogyakarta Tahun 2017 - Khairunissa Balqis Zhahira; Efri Diah Utami (Politeknik Statistika STIS, 2021)
Yogyakarta Province is ranked as the 8th happiest province in Indonesia, which is 72.93. Although Yogyakarta has a fairly high Happiness Index rating, Yogyakarta Province has several problems from an economic perspective. First, the percentage of poor people in Yogyakarta in March 2017 was 13.02 percent and in September 2017 it was 12.36 percent, this percentage is above the national average percentage of poor people. Second, the Gini ratio of Yogyakarta is 0.432, this causes the Gini ratio of Yogyakarta to be the highest in all provinces of Indonesia, and the third problem, in 2017 the Provincial Minimum Wage (UMP) Yogyakarta is the smallest UMP in all of Indonesia, which is Rp. 1,337,645. Therefore, this study aims to determine the general description and variables that affect the level of happiness of the Yogyakarta population in 2017. The method used is Ordinal Logistics Regression. The results showed that the level of happiness of the people of Yogyakarta was influenced by the variables of age, income, savings ownership, and did not experience health problems.